Effect of Organic Fertilizer Doses of Coal And Mutiara NPK on The Growth of Grafting Yields of Pomelo Seedlings (Citrus grandis L. Osbeck) - Ni Komang Ayu Aryawati Dewi; Made Sri Yuliartini; Ida Bagus Komang Mahardika (SEAS (Sustainable Environment Agricultural Science), 2022)
This study aims to determine the effect of giving a dose of organic coal fertilizer and NPK fertilizer on the growth of grafting seedlings of pomelo varieties. This research is an experiment on polybag planting media conducted at UPTD. Balai Benih Tanaman Pangan dan Hortikultura of Bali Province from February to July 2022. This study was arranged based on a Completely Randomized Block Design (RCBD) with 2 factors arranged in a factorial manner. The first factor is the dose of coal organic fertilizer (B) consisting of 4 levels: B0: 0 gr/polybag, B1: 71 gr/polybag, B2: 142 gr/polybag, B3: 213 gr/polybag. The second factor was the dose of NPK (N) consisting of 4 levels: N0:0 g/polybag, N1: 18.75 g/polybag, N2:37.5 g/polybag, N3:56.25 g/polybag. Thus, there were 16 treatment combinations, each of which was repeated 3 times to obtain 48 polybags. The results of statistical analysis showed that the interaction (BÃ—N) and 0.05) on shoot growth variables (days), shoot cultation length (cm), bud grafting diameter (mm), number of leaves (strand), total leaf area (cm2). The fastest rootstock cuttings were obtained with a dose of NPK fertilizer of 37.5 g/polybag (N2) which was 6.67 days and the difference was not significant at a dose of 18.75 g/polybag (N1) which was 7.42 days. Keywords : dose, coal fertilizer, npk fertilizer, grafting, pomelo